Dimensi Gender dalam Pengetahuan tentang Iklim dan Perubahan Iklim pada Masyarakat Pertanian - Salsabilla Shofia (Umbara, 2021)
Climate change requires people to find the best strategy to adapt. One way to find an effective strategy is to identify knowledge about climate and climate change in the community. This knowledge is inseparable from the gender dimension. By understanding the gender dimension in knowledge about climate and it changes in society, this study can contribute to find effective adaptation strategies in coping climate change. This article was written using the literature study method, by classifying and analyzing secondary data from various article sources in the form of case examples in various regions. The results show that there are differences between women's and men's knowledge about climate, both how to predict the weather and climate, as well as changes in climate variability and the causes of change. In terms of climate predictions knowledge, women pay more attention to climate prediction indicators in the neighborhood where they live, while men pay more attention to climate prediction indicators around the fields where they work. In terms of knowledge about climate change, there are differences in knowledge about the causes of climate change. Women have less knowledge about the causes of climate change than men. This is because women experience limited access to education and sources of information. A just and sustainable climate adaptation strategy needs to take gender dimensions into account and involve women and men equally, because gaps in the level of knowledge will hinder strategies for adapting to climate change.